Primary Pulmonary Hydatid Disease - Alam, Md Tarek; Saber, Sadia; Alam, Rafa Faaria; Hossain, Mohammad Monower (Bangladesh Critical Care Journal, 2018)
Echinococcosis is a parasitic disease endemic in many parts of the world. Liver is the most common affected organ followed by lungs. However, the infestation of the latter is usually secondary to another infected organ system. Symptoms are not specific and can be produced by the mass effect or cyst complications. In the article we are reporting a case of pulmonary echinococcosis in a middle aged male, where the patient presented with symptoms of fever, cough with expectoration, weight loss and dysponea. An extensive work-up showed no other foci of infestation, hence final diagnosis was done based on chest radiography and tomography scan findings and was successfully treated with Albendazole. Bangladesh Crit Care J September 2018; 6(2): 105-107